Cancer vaccines in the clinic - Morgan E. Janes; Alexander P. Gottlieb; Kyung Soo Park; Zongmin Zhao; Samir Mitragotri (Wiley, 2024)
Abstract Vaccines are an important tool in the rapidly evolving repertoire of immunotherapies in oncology. Although cancer vaccines have been investigated for over 30 years, very few have achieved meaningful clinical success. However, recent advances in areas such antigen identification, formulation development and manufacturing, combination therapy regimens, and indication and patient selection hold promise to reinvigorate the field. Here, we provide a timely update on the clinical status of cancer vaccines. We identify and critically analyze 360 active trials of cancer vaccines according to delivery vehicle, antigen type, indication, and other metrics, as well as highlight eight globally approved products. Finally, we discuss current limitations and future applications for clinical translation of cancer vaccines.